A preliminary study on the production of dry rice-based starter for rice wine making - Chavoso, Johanna W. (1997.)
An experimental method in producing dry rice-based starter for rice wine making was developed to standardize existing indigenous methods.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Rice wines; Rice-based starter